Definition of a Global Coordinate System in the Foot for the Surgical Planning of Forefoot Corrections - Sanne Krakers; Anil Peters; Sybrand Homan; Judith olde Heuvel; Gabriëlle Tuijthof (Biomechanics, 2023)
Forefoot osteotomies to improve the alignment are difficult procedures and can lead to a variety of complications. Preoperative planning in three dimensions might assist in the successful management of forefoot deformities. The purpose of this study was to develop a global coordinate system in the foot for the planning of forefoot corrections. Two strategies (CS1 and CS2) were developed for defining a global coordinate system that meets the criteria of being well-defined, robust, highly repeatable, clinically relevant, compatible with foot CT scans, independent of the ankle joint angle, and does not include bones in the forefoot. The absolute angle of rotation was used to quantify repeatability. The anatomical planes of the coordinate systems were visually inspected by an orthopedic surgeon to evaluate the clinical relevancy. The repeatability of CS1 ranged from 0.48° to 5.86°. The definition of CS2 was fully automated and, therefore, had a perfect repeatability (0°). Clinically relevant anatomical planes were observed with CS2. In conclusion, this study presents an automated method for defining a global coordinate system in the foot according to predefined requirements for the planning of forefoot corrections.